A statistical evaluation of the corrosion behaviour of friction stir welded AA2024 aluminium alloy. (2020) - Seetharaman, R.; Seeman, M.; Kanagarajan, D.; Sivaraj, P.; Saravanan, I.
Abstract: In this research, response surface methodology (RSM) was used to analyse the effect of pH value, immersion time and chloride ion concentration on the corrosion rate of friction stir welded AA2024 aluminium alloy. A rotatable central-composite design was used to develop models for the responses. From the analysis of residuals it is possible to conclude that they were randomly distributed around zero, and there was no evidence of outliers. The higher value of R 2 is better to determine the coefficients of regression equation. So the coefficient in the regression equation for corrosion rate could be determined more effectively. The closeness of the adjusted R 2 with R 2 determines the fitness of model. The model found was further evaluated with test experiments and the results were then compared with predicted values.